Translation in the Teaching of a Foreign Language As a Means and As an End - Suparmin Suparmin (TEFLIN, 2003)
In the history of foreign language teaching translation has alternately been praised and condemned. Unfortunately, the praise and condemnation were based on a rather simplistic, biased, and extreme view of the role of translation. In this view no clear, explicit distinction was made between translation as a means and as an end although in practice people already showed a tendency to be more concerned with one aspect than the other. Moreover, in their treatment of translation people tended to take an Ã¢â¬Åeither Ã¢â¬Â¦ or Ã¢â¬Â¦Ã¢â¬Â position. Either take it or leave it. This paper proposes a more explicit, balanced, and moderate attitude towards translation and its two aspects. It is suggested that a clear distinction be made between translation as a means and as an end and that each be treated accordingly in a better programmed way. The treatment should consider the level of instruction. At the beginning level translation should be treated more as a means than as an end. Gradually, as the level of instruction progresses the role of translation as a means is reduced, while its role as an end is increased so that at the more advanced levels translation will be treated more as an end than as a means. Accordingly, translation should not be totally abandoned or too liberally used. However, the use and disuse should be based on a careful and well-prepared program. In line with the idea that translation be treated as an end at the more advanced level, and considering its importance for a developing nation, it is also proposed here that translating be adopted as a Ã¢â¬Åfifth skillÃ¢â¬Â to be pursued.